2002
DOI: 10.1086/340853
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and Stress‐Induced Levels of Corticosterone during Different Life Cycle Substages in a Shorebird on the High Arctic Breeding Grounds

Abstract: Baseline and stress-induced levels of corticosterone during different life cycle substages in a shorebird on the high arctic breeding grounds Reneerkens, J; Morrison, RIG; Ramenofsky, M; Piersma, Theun; Wingfield, JC Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 21 publications
5
19
0
Order By: Relevance
“…The average baseline corticosterone concentration of the red knots in our study (15.7 before and 14.00 ng/ml after the experimental flights, see Fig. 1) is within the range reported in other studies on the same species (10-30 ng/ml; Piersma and Ramenofsky, 1998;Reneerkens et al, 2002). Hence, it seems very unlikely, that the baseline levels were affected by the immune challenge the knots experienced before the flight experiments (Hasselquist et al, 2007).…”
Section: Fixed Effectssupporting
confidence: 88%
See 1 more Smart Citation
“…The average baseline corticosterone concentration of the red knots in our study (15.7 before and 14.00 ng/ml after the experimental flights, see Fig. 1) is within the range reported in other studies on the same species (10-30 ng/ml; Piersma and Ramenofsky, 1998;Reneerkens et al, 2002). Hence, it seems very unlikely, that the baseline levels were affected by the immune challenge the knots experienced before the flight experiments (Hasselquist et al, 2007).…”
Section: Fixed Effectssupporting
confidence: 88%
“…Elevated baseline levels of corticosterone have been observed in several species during the migratory period at rest and just after endurance flight, when the birds have landed (O'Reilly and Wingfield, 1995;Holberton et al, 1996;Landys-Ciannelli et al, 2002;Reneerkens et al, 2002). It is hypothesized that during a phase of increased energy demands hormone action maintains the metabolism within a heightened operating range, defined as state B by McEwen and Wingfield (2003).…”
Section: Introductionmentioning
confidence: 99%
“…These birds also had no elevated corticosterone, except in a few which had completely emaciated breast muscles and no visible fat. The baseline corticosterone values of all birds in our study were very similar to those of wild red knots at their breeding grounds (Reneerkens et al, 2002) and to apparently unstressed red knots that had long been adjusted to living in indoor cages . Similarly low values were found in refuelling bar-tailed godwits Limosa lapponica Linnaeus in the wild (Landys-Ciannelli et al, 2002), whereas red knots and godwits newly arrived following long flights had substantially higher corticosterone levels (Reneerkens et al, 2002;LandysCiannelli et al, 2002).…”
Section: Discussionsupporting
confidence: 64%
“…Birds were removed from aviaries once every week so that aviaries could be cleaned and were weighed and checked for general health status at this time. Piersma et al (2000) and Reneerkens et al (2002) suggested that corticosterone levels in migrating red knots increase specifically in association with migratory flight. To corroborate these findings, we first investigated plasma levels of corticosterone in captive birds during spring migration (May-June) in the year 2000.…”
Section: Animalsmentioning
confidence: 99%
“…For example, when held in captivity on their wintering grounds, red knots show an increase in plasma corticosterone only after having attained a body mass similar to that of departing conspecifics (Piersma et al 2000). Also, free-living red knots display elevated corticosterone at the conclusion of a long bout of migratory flight, as they arrive at their breeding grounds in the North American Arctic (Reneerkens et al 2002). The correlation between corticosterone and migratory flight in this species suggests that corticosterone may be involved in the onset and regulation of migratory movements and correlated physiological processes.…”
Section: Introductionmentioning
confidence: 99%